A-novel adjustable pre-pressure ultrasonic motor designed for variable temperature rotational speed environments - Liu, Xiaopeng; Wang, Jiru; Yan, Langlang; Mao, Dubang; Tong, Baoshan; Zhao, Hongwei (Precision engineering, 2025)
The traveling wave ultrasonic motors (TWU-motors), operating based on the friction drive method have the advantages of low speed and large torque, fast response speed, no electromagnetic interference. However, the friction driving effect is very sensitive to the changes of the pre-pressure and friction contact area, and the inappropriate contact mode will not only reduce the performance of the TWU-motor, but also accelerate the wear of the TWU-motor and produce noise. In this study, we propose a novel TWU-motor design that incorporates a flexible rotor (FR) to enhance both speed and load capacity. The FR is designed to increase the contact area between the rotor and stator. Furthermore, the stator structure and rotor vibration performance of the TWU-motor were optimized through experiments and finite element simulations. An experimental setup was constructed to evaluate the electromechanical performance of the TWU-motor and to test how its performance varies with changes in ambient temperature. Experimental results revealed that the TWU-motor achieved a maximum rotational speed of 101 r/min, a minimum speed of 1 r/min, a peak torque of 878 mN m, and maintained normal operation within a temperature range of 20 °C–190 °C. This study has potential applications in camera autofocus systems, precision control of miniature robots, and spacecraft control systems. •Flexible rotor sustains friction stability across 20–190 °C for aerospace/robotics.•Tail bolt-pressure coupling mechanism achieves 0.878 N m torque at 300 Vpp.•Damping rubber coating reduces noise by 40 % via simulation-guided rotor optimization.•70 × 70 × 64 mm3 actuator enables precise control in cameras and spacecraft systems.